Prevalensi Nyeri Leher Terkait Kinerja Dan Faktor Resikonya Pada Pegawai Di RS.Mitra Keluarga Surabaya - Darmawan, Dwi; Abdullah, Ahmad; Kasimbara, Rachma Putri; Fau, Yohanes Deo (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: The performance system is a process carried out by employees when carrying out a job, operating work tools related to work posture and duration of work that produces something concrete that can be measured. To achieve good performance, the comfort aspect while working is very important. Neck pain is one of the problems that are often felt by employees with risk factors. Neck pain is an uncomfortable sensation that arises in the neck that brings unpleasant things related to actual or potential damage, both specific and non-specific. The cause of neck pain is influenced by several factors including; musculoskeletal factors, nervorum factors, vascularization factors, and joint factors.Methods: This type of research uses a case-control design analysis and observation using an observational approach with a questionnaire as a tool. The independent variables in this study were risk factors while the dependent variable was the prevalence of neck pain. The sample size in this study was 30 employees of the Mitra Keluarga Hospital Surabaya who worked in a sitting position using computer work equipment and were divided into 2 groups. Both groups were given a questionnaire to collect data, after the data was collected then its prevalence was analyzed.Results: Neck pain is one of the problems that is often felt by employees of Mitra Keluarga Surabaya Hospital where researchers have conducted research on the prevalence of neck pain related to performance and its risk factors which shows 66.6% of employees of Mitra Keluarga Surabaya Hospital feel pain in the neck due to risk factors.Conclusion: The prevalence of neck pain among employees at Mitra Keluarga Hospital, Surabaya, related to their performance and performance factors, is 66.6%.